Efeitos da clorexidina nanoencapsulada sobre a cavidade oral em humanos - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2019)
Chlorhexidine is considered a antiseptic with bactericidal action in both gram-positive and gram-negative bacteria, as well as bacteriostatic action, since it prevents bacterial proliferation. It can be used to control supragingival plaque and maintain the health of teeth and oral mucosa tissue. However, the use of oral antiseptics is controversial because, despite their effectiveness in controlling several pathogenic bacteria, they may have a genotoxic potential in the oral mucosa epithelium in individuals who use this substance. This research aimed to answer the question about the use of 0.12% nanoencapsulated chlorhexidine and it`s efficacy in the oral cavity compared to commercially available chlorhexidine. It was a four arm, randomized controlled, parallel, triple-blind prevention trial with a sample of 32 participants, separated into 4 groups with 8 members each, who received different mouthwash substances: chlorhexidine nano. , vehicle (ethanol), commercially obtained chlorhexidine and placebo (zein). Oral examination, oral epithelial cell collection and quantitative and qualitative questionnaires were performed before and after the use of mouthwash and the micronucleus test. It was observed that nanoencapsulated chlorhexidine reduced gingival bleeding, also allowing a reduction in the presence of periodontal pockets and didan´t change the dental color, however favored the accumulation of dental calculus and was the substance that presented the most unpleasant taste to the study participants. As for the frequency of micronuclei, there was no change, showing that this substance has no genotoxic effects within 10 days of the study.
Keywords: Clorexidina; Antissépticos Bucais; Cavidade Bucal; Testes de Genotoxicidade; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA::PERIODONTIA